A national framework for managing dual-use research of concern: integrating biosecurity, public health, and research governance - Ruihan Zhang (Frontiers in Bioengineering and Biotechnology, 2026)
Dual-use research of concern (DURC)—legitimate life-science research that could be misapplied to cause significant harm—has become an increasingly urgent policy challenge. Advances in synthetic biology, gene editing, and artificial intelligence have expanded both the pace and diffusion of high-risk biological work, while governance systems remain fragmented across national boundaries. Based on a structured narrative policy review updated through 28 July 2026, this article proposes a comprehensive national DURC risk-management program that bridges biosecurity, public health, research governance, and emergency management. Drawing on the World Health Organization’s 2022 Global Guidance Framework for the Responsible Use of the Life Sciences, the ISO 35001:2019 biorisk management standard, and national policy precedents—including the design of the 2024 U.S. Government Policy for Oversight of Dual Use Research of Concern and Pathogens with Enhanced Pandemic Potential (DURC-PEPP Policy), whose planned implementation was superseded by Executive Order 14,292 while a revised or replacement federal policy remained under development at the final search date—the article maps five overlapping threat pathways relevant to DURC governance, analyzes their multi-layered consequences, and identifies existing tools and stakeholder interfaces that can be adapted. The core of the framework comprises eleven integrated recommendations across prevention and response domains: establishing a national DURC governance structure, strengthening institutional oversight and ethics review, implementing laboratory biorisk management systems, addressing cyberbiosecurity, mitigating insider threats, promoting responsible communication safeguards, enhancing early detection and surveillance, developing DURC-specific emergency response plans, protecting first responders and healthcare workers, institutionalizing risk communication and public engagement, and embedding continuous learning and international collaboration. The program emphasizes the protection of frontline workers, the integration of occupational health into biosecurity planning, and the institutionalization of intersectoral coordination mechanisms. Achieving these goals requires sustained collaboration across health, security, research, digital, and community sectors, but the benefits extend beyond DURC, enhancing national preparedness for all biological threats.